Perlindungan Hukum Terhadap Penumpang Atas Pelanggaran Hak Kenyamanan, Keamanan dan Keselamatan di PT Garuda Indonesia Persero - Andrea Citra Brilliantina; Retno Wulansari (Prosiding Seminar Hukum Aktual Fakultas Hukum Universitas Islam Indonesia, 2024)
This research is discuss about legal protection for passengers violations of their rights to comfort, security and safety at PT. Garuda Indonesia Persero. The problem in this research are regarding legal protection for passangers violations of their rights and legal responsibility protection of PT. Garuda Indonesia Persero for passangers whose rights are violated. This research used normative legal research, that used case approach and legislation. This research used qualitative data analysis. The results this research are first, the rights of comfort, security and safety of passangers are not full filled. Second, responsibility of airline towards passengers is not consistant with the services promised.